2018
DOI: 10.1016/j.jmmm.2018.02.078
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and dipole moments in indium doped barium hexaferrites

Abstract: Crystal and magnetic structure of the doped BaFe12-xInxO19 samples were refined by the results of investigations using high resolution neutron powder diffraction and vibration sample magnetometry at different temperatures. The refinements were realized in frame of two space groups. The P63/mmc (No 194) centrosymmetric nonpolar and P63mc (No 186) noncentrosymmetric polar space groups were used. The unit cell parameters, ionic coordinates, thermal isotropic factors, occupation positions, bond lengths and bond an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(30 citation statements)
references
References 77 publications
(96 reference statements)
4
24
0
Order By: Relevance
“…186). The latter one is a non-centrosymmetric space group and is generally used to describe the crystal structure in order to explain the existence of non-zero spontaneous polarization [18,19]. These ferrites are usually termed as hard ferrites because of their high electrical resistivity, saturation magnetization, coercivity, and mechanical hardness [20].…”
mentioning
confidence: 99%
“…186). The latter one is a non-centrosymmetric space group and is generally used to describe the crystal structure in order to explain the existence of non-zero spontaneous polarization [18,19]. These ferrites are usually termed as hard ferrites because of their high electrical resistivity, saturation magnetization, coercivity, and mechanical hardness [20].…”
mentioning
confidence: 99%
“…Such trend was also observed and reported by Teh and Jefferson. It caused the volume of unit cell to reduce [5,13]. Grain size (Fig.…”
Section: Structural Analysismentioning
confidence: 99%
“…Researchers have also reported that these properties can be modified by substitution of magnetic and nonmagnetic elements. For this, substitution like Al, Sc and Ga particularly oxide dopants like B 2 O 3 , Si 2 O 3 and CaO not only modify the growth and morphology but also induce fascinating properties [5]. These properties are modified due to microstructural variations in lattice parameters, particle growth and their morphology.…”
Section: Introductionmentioning
confidence: 99%
“…For example, anion-deficient perovskites, as materials with high ionic conductivity and a wide range of temperature stability, are very suitable for fuel cell membranes [19]. Moreover, magneto dielectrics such as hexaferrites: are the materials that are promising for the production of capacitors, which are very necessary for their stable operation [20]. For the stable and steady operation of modern power plants and uninterruptible power systems, it is necessary to provide for their protection against unwanted external electromagnetic radiation.…”
Section: Introductionmentioning
confidence: 99%